Stress and Coping Among Elderly During The COVID-19 Pandemic in Sulaimanya City in Kurdistan Region of Iraq - Qadr, Yousif Abdalla; Ismail, Azad Ali (Kurdistan Journal of Applied Research, 2023)
This study aimed to find out the level of stress and coping methods among elderly in Sulaimanya city during the pandemic COVID-19. Through the snowballing sampling method, 394 elders were included to this study. After validation, two scales were used in this study; stress subscale from Depression, Anxiety and Stress Scale (DASS-21) and a culture-bound scale for determining coping methods. The results of this study showed that participants experienced a mild level of stress. Male participants, elders who live with their family, unvaccinated elders, physically passive elders have had higher stress level than female, elderly home, vaccinated, physical active elders. The findings also indicated that spiritual connection was the most common coping method used by the sample. Results of this study are the first and foremost way to share elder’s unexpressed messages; it also can be a way for verbalizing their unspoken feelings. These results may also inform the elder’s caregivers that elder’s stress level and illness anxiety was not very high, strengthening their social support and spiritual connection may help them to reduce their distress into a lesser degree.